IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF BERBASIS TEKNOLOGI AUGMENTED REALITY UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Syaifur Rizal; Choerul Anwar Badruttamam; Nani Zahratul Mufidah (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
This study aims to improve student learning outcomes in science subjects through the assistance of a Cooperative Learning Model Based on Augmented Reality (AR) Technology. The research approach used is qualitative research, using Observation, Interview, and Documentation Techniques. Data analysis was carried out by data reduction, data presentation, and conclusions. This study was conducted at one of the Nahdlatul Ulama Elementary Madrasah institutions in Blado Wetan Village, Banyuanyar District, Probolinggo Regency, with 22 research subjects. The findings from the results of this study indicate that the use of the Cooperative Learning Model with the Assistance of Augmented Reality (AR) technology greatly helps students to improve their learning outcomes. The majority of all students feel very helped in understanding difficult material to be easier with the help of Augmented Reality (AR) technology. Students also actively collaborate with other friends in solving a problem in learning. These results show a positive thing for improving student learning outcomes in the context of science learning. This study can provide valuable insights for teachers in developing technology-based learning models in the field of education.